Wireless Sensing for the Respiratory Activity of Human Beings: Measurements and Wide-band Numerical Analysis - Lorenzo Scalise; Valter Mariani Primiani; Paola Russo; Alfredo De Leo; Desar Shahu; Graziano Cerri (International Journal of Antennas and Propagation)
An electromagnetic sensing system for the measurement of the respiratory activity is presented. The aims are to demonstrate the feasibility of the proposed approach and in particular to evaluate the effect on the measured signal of the distance between the subject and the sensing apparatus. Moreover, an electromagnetic model of the system, including the monitored subject, is proposed as a tool to solve the problem of selecting working parameters for system design. The sensing system is based on the measurement of the phase variation of the reflection coefficient caused by the respiratory activity. The phase signal compared with the thorax displacement measured by a reference instrument shows a high correlation () for different subject postures (sitting, standing, and lying) and a reduction of the signal amplitude with the distance  dB/cm is reported. The numerical simulations performed on a wide-band highlight the frequencies where the method exhibits the highest sensitivity to thorax movements. The sensitivity can be further improved by reducing the antenna beamwidth. Despite the signal amplitude reduction, the proposed system makes it possible to correctly operate at distances up to 2.5 m.